COVID-19: psychosociological phenomenon and implications for nursing - Rosa Maria Ferreira de Almeida; Ana Beatriz Azevedo Queiroz; Márcia de Assunção Ferreira; Rafael Celestino da Silva (SciELO, 2021)
ABSTRACT The objective was to reflect on COVID-19 as a phenomenon of social representations and its implications for nursing and health. A theoretical-reflective study, guided by the precepts of social representations. Reading of scientific articles and books on social representations and official data on COVID-19 were sources for further analytical analysis in the light of theory. COVID-19 is a psycho-sociological phenomenon as it meets the criteria of relevance and practice, in addition to having an imagery and symbolic dimension that circulates in the mass media. There is a projective dimension of the disease by different social groups. The different daily behaviors express a socio-symbolic logic about the phenomenon. The criteria of relevance and practice, the image about the disease and its symbolic dimension support COVID-19 as a phenomenon of social representations, whose research has the potential to improve effective communication with the population, with a view to adherence to preventive care practices to infection.